Micronutrient Deficiencies and Digital Computerized Phototrichogram Analysis in Telogen Effluvium: A Retrospective Correlation Study in a Tertiary Medical Center - Hakan Arslan; özgür gündüz (Mattioli1885, 2023)
Introduction:Telogen effluvium (TE) is a common form of non-scarring alopecia that may manifest as acute or chronic hair shedding. Several studies evaluated a possible relationship between various vitamin and mineral deficiencies and TE, but it is still a controversial topic. Objectives: This study aimed to investigate the status of vitamin and mineral deficiencies in patients diagnosed with TE and to evaluate their correlation with anagen hair ratios (AHR) calculated with an automated digital phototrichogram (ADCP). Methods:Electronic records of 973 TE patients were retrospectively analyzed. Demographic, clinical data, parameters such as ferritin, vitamin B12 (Vit-B12), vitamin D (Vit-D), folic acid, zinc and hemoglobin (HGB) serum levels were evaluated. Anagen to telogen hair ratios were also assessed in forty-two patients via ADCP. Results: The rates of anemia, low ferritin level, and Vit-B12, folate, Vit-D, and zinc deficiencies were 11.9% (N = 109), 44% (N = 332), 1.5% (N = 13), 2.5% (N = 14), 87% (N = 51), and 4.5% (N = 2), respectively. A positive correlation was found between HGB levels and AHR in female patients (Spearman rank, r = 0.417, P = 0.008). No statistically significant relationship was found between ferritin, Vit-B12, folate, zinc serum levels and AHR. The relationship between Vit-D and AHR could not be assessed due to the insufficient number of patients with Vit-D data. Conclusions:HGB value is the only marker that is positively correlated with the AHR of patients with TE. Ordering HGB can be used as an initial test for managing TE patients cost-effectively.